An interpolation of Ohno's relation to complex functions - Hirose, Minoru; Murahara, Hideki; Onozuka, Tomokazu (Mathematica Scandinavica, 2020)
Ohno's relation is a well known formula among multiple zeta values. In this paper, we present its interpolation to complex functions.